(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Maternal psychiatric disorders during pregnancy and the postpartum period are associated with adverse outcomes both for the mother and offspring in the long term, which increases the risk of poor mother-infant bonding and delays in infant development. The study aimed to assess the psychiatric morbidities among postnatal women in a tertiary care hospital. Method: A cross-sectional study was conducted in Patan Hospital, Lalitpur, among 165 postnatal women using a purposive sampling technique from April 2020 to May 2021. Data was collected by the face-to-face interview technique using a structured interview schedule. Psychiatric morbidities were examined by using the Nepalese version of the Depression Anxiety Stress Scale 21 (N-DASS 21) and the Nepalese Version of the Edinburgh Postnatal Depression Scale (N-EPDS). Data were analyzed by using SPSS version 16. Descriptive statistics were used to analyze demographic variables. Chi-square and Fisher’s exact test were used to examine the association between independent variables and psychiatric morbidities. Result: The psychiatric morbidities were found among 56(34.51%) of postnatal women. Among them, postnatal depression 19(11.31%), anxiety 21(13.33%) and stress 16(9.67%) were prevalent. The gender of the baby was significantly (χ2 =6.382, p=0.012) associated with anxiety. No significant associations were found between other sociodemographic or obstetric variables and postnatal depression, anxiety, or stress. Conclusion: Anxiety is more prevalent than postnatal depression and stress among postnatal women. The baby’s gender is significantly associated with anxiety.